Tongmai Yangxin pill reduces myocardial no-reflow by regulating apoptosis and activating PI3K/Akt/eNOS pathway. (28th October 2020) - Chen, Rui; Chen, Ting; Wang, Tianqi; Dai, Xiangdong; Meng, Ke; Zhang, Shuying; Jiang, Di; Wang, Yanyan; Zhou, Kun; Geng, Tong; Xu, Jinpeng; Wang, Yi
Abstract: Ethnopharmacological relevance: Tongmai Yangxin pill (TMYX) is derived from the Zhigancao decoction recorded in Shang han lun by Zhang Zhongjing during the Han dynasty and was further improved by Professor Ruan Shiyi, a cardiovascular expert at Tianjin University of Traditional Chinese Medicine. TMYX is used for the clinical treatment of chest pain, heartache, and qi-yin-deficiency coronary heart disease and can improve vascular endothelial function in patients with angina pectoris or coronary heart disease by up-regulating nitric oxide activity and then regulating vascular tension. Whether TMYX can further improve myocardial no-reflow by up-regulating NO activity and then dilating blood vessels remains unclear. Aim of the study: This study aimed to reveal whether TMYX can further improve myocardial NR by up-regulating NO activity and then dilating blood vessels. The mechanism underlying PI3K/Akt/eNOS pathway activation and apoptosis regulation is also explored. Materials and methods: The left anterior descending coronary arteries of healthy adult male SD rats were ligated to establish a NR model. The rats were assigned to 14 groups: control, sham, NR, TMYX (4.0 g/kg), sodium nitroprusside (SNP), Tongxinluo capsule (TXL), PI3K blocker (LY), TMYX + LY, SNP + LY, TXL + LY, eNOS blocker (L-NAME), TMYX + L-NAME, SNP + L-NAME, and TXL + L-NAME groups. Cardiac function was measured through echocardiography. Thioflavin S, Evans Blue, and TTC staining were adopted to evaluate NR and ischemic areas. Cell inflammation degree and edema were assessed by hematoxylin–eosin staining. Automated biochemical analyzer and kit were used to detect the activities of myocardial oxidants, including reactive oxygen species, super oxide dismutase, malonaldehyde, and NO. The expression levels of genes and proteins in the PI3K/Akt/eNOS signaling pathway and apoptosis were detected via real-time fluorescence quantitative PCR and Western blot analysis, respectively. A microvascular tension sensor was adopted to detect coronary artery diastolic function in vitro. Results: TMYX reduced NR and ischemic areas; suppressed LV-mass; enhanced EF, FS, LVOT peak, and LVSV; and improved cardiac structure and function. Moreover, it decreased creatine kinase (CK), CK-MB, and lactic dehydrogenase activities. TMYX increased NO and super oxide dismutase activities; inhibited malonaldehyde activity; reduced muscle fiber swelling and inflammatory cell infiltration; and improved vasodilation in vitro. In the NR myocardium, TMYX stimulated myocardial PI3K activities and PI3K (Tyr458) phosphorylation and enhanced Akt activities and Akt phosphorylation at Tyr315. TMYX increased the activities of eNOS and the phosphorylation of eNOS at Ser 1177 in the NR myocardium and attenuated cardiomyocyte apoptosis by increasing the expression of Bcl-2 and decreasing that of caspase-3 and Bax. All these effects of TMYX were abolished by the specific inhibitors of PI3K (LY) and eNOS (L-NAME). Conclusions: TMYX attenuates myocardial NR after ischemia and reperfusion by activating the PI3K/Akt/eNOS pathway and regulating apoptosis, further up-regulating NO activity and relaxing coronary microvessels. Graphical abstract: Image 1 Highlights: TMYX improved the area of no-reflow and ischemia, and increased the content of NO, SOD activity and vasodilating function. TMYX enhanced PI3K activities, stimulated Akt activities and increased eNOS activities. TMYX increased the expression of Bcl-2, decreased Caspase-3 and Bax expression. TMYX improved no-reflow by activating PI3K/Akt/eNOS pathway and regulating apoptosis.